Fostering niches among SMEs in Malaysia through organizational commitment, leadership, organizational culture and job satisfaction - Gallato, Cristina G.; Rashid, Safiah; Warokka, Ari; Reamillo, Kristy Aireen G.; Abdullah, Haim Hilman (IBIMA Publishing, 2012)
Niche creation is a challenge among firms regardless of size, ownership and the kind of product/service they offer. Once it is created, fostering such niche becomes a greater issue.In this paper, we focused on the SMEs in emerging markets particularly in Malaysia.By using questionnaires, data was gathered from 100 employees working in SMEs particularly in Selangor, Malaysia.The purpose of this study is to let owners/managers/founders of SMEs better understand how fostering niches is influenced by organizational commitment,leadership, and organizational culture, towards job satisfaction as antecedents of competitive advantage and/or success of SMEs. Employees’ attitudes and behaviours are affected by the relationship between them and their employer.This relationship is referred to as organizational commitment.Moreover, leadership and organizational culture considerably have an influence on job satisfaction.Understanding this concept will aid employers to instil strong organizational culture and create solid organizational commitment among their employees and lead effectively so that they would be able to retain their well-experienced and skilful employees. Ultimately job satisfaction plays a very important role in the success of organizations particularly in the context of SMEs in Malaysia. The findings revealed positive relationships among the variables and their importance as determinants of job satisfaction in SMEs, which hopefully could contribute to the extant literature on job satisfaction and competitive advantage from the perspective of this country in Asia.